Kualitas Air Sungai pada Berbagai Tipe Penutupan Lahan pada Sub-sub DAS di DAS Latuppa - Fauziyah Abidin; Syamsuddin Millang; Usman Arsyad (Jurnal Hutan dan Masyarakat, 2019)
Water has an important role in life. The use of water in various activities must be based on water quality which is influenced by various aspects, one of it is land cover. This study aims to determine water quality, water quality standards and the effect of land cover on water. This study took samples at six points to determine the physical and chemical quality of water. The results showed that the chemical and physical quality of water in the Latuppa watershed still met water quality standards when there was no rain. Parameters that did not meet when rain occurred in the form of turbidity, TSS, and BOD in the river water of the Latuppa watershed. Water quality of the Siguntu Sub-watershed and the Mangkaluku Sub-watershed in the Latuppa River Basin is still relatively good for the use of raw water for drinking water. The water quality in the Latuppa watershed which is covered by forest land (Siguntu Sub-watershed and Mangkaluku Sub-watershed) is better than non-forested (Rantenase Sub-watershed).